Household income and child well-being in Japan: The role of grandparental coresidence and residential proximity. (April 2020) - Wang, Jia; Raymo, James M
In this study, we examined whether and how the income gradient in child well-being may vary by grandparental coresidence and proximate residence in Japan, a country characterized by a high prevalence of intergenerational proximity and intensive family investment in children's development. Using data from the Japan Child Panel Survey, we first demonstrated that household income is positively associated with multiple dimensions of children's well-being, a relationship that was particularly strong for cognitive skills. We also found that children from lower-income families were more likely to coreside with grandparents than their counterparts from middle- and higher-income families, and that children from both lower- and higher-income families had similar likelihoods of living near their grandparents. However, children in lower- and higher-income families who coresided with grandparents had lower math and Japanese test scores than those living at a distance. These relationships resulted in smaller income gradients in test scores for children coresiding with grandparents and near their grandparents, relative to those whose grandparents lived farther away. International comparisons showed that the income gradient in children's academic performance is largest in the US and smallest in urban China, with Japan being in the middle, and that multigenerational coresidence is generally associated with worse cognitive outcomes for children in both lower- and higher-income families across these three very different contexts. These findings provide new insights into the complex ways in which intergenerational proximity is related to economic disparities in children's well-being.